INFLUENCE OF DIGITAL SERVICE QUALITY ON USER SATISFACTION OF THE TV PERÚ DIGITAL PLATFORM, 2024 - Franco Ulco, Roberto (2025)
The research was developed with the purpose of determining the influence of the quality of digital service on the satisfaction of users of the TVPerú digital platform during the year 2024. From this, a quantitative approach, explanatory level and non-experimental design were used, the sample consisted of 384 users, the data collection technique was the survey and the instrument was a questionnaire of 29 questions on a Likert scale and the methodology was multiple linear regression. The results showed a significant influence (p-value of 0.000) of the dimensions of information quality (33.4%), security (15.4%), interactivity (18%) and system quality (17.6%) on satisfaction. The model obtained an R2 of 0.470 and a p-value of 0.000, so it is concluded that the quality of digital service influences the satisfaction of users of the TVPerú digital platform. The government's digital platforms are vital for promoting transparency, access to information, and participation in public services. They also reflect the government's interaction and bring it closer to citizens. The importance of this study lies in understanding the factors that explain satisfaction and in promoting such use.